copolymer of ethylene and 1,3-diene

KR103019569B1Active Publication Date: 2026-09-16꽁빠니제네날드에따블리세망미쉘린
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020227024696
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-18
Filing Date
2020-12-14
Publication Date
2026-09-16
Estimated Expiration
2040-12-14

Smart Images

  • Figure 112022074171086-PCT00001
    Figure 112022074171086-PCT00001
  • Figure 112022074171086-PCT00002
    Figure 112022074171086-PCT00002
  • Figure 112022074171086-PCT00003
    Figure 112022074171086-PCT00003
Patent Text Reader

Abstract

The present invention relates to a copolymer of ethylene and 1,3-diene containing 50 mol% or more of ethylene units and 1,2-cyclohexanediyl units, wherein the 1,3-diene is 1,3-butadiene or a mixture of 1,3-diene containing 1,3-butadiene, and the copolymer comprises one main chain and one or more side chains.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The field of the present invention relates to highly saturated diene copolymers containing ethylene and 1,3-butadiene units.

[0002] The most widely used diene elastomers in tire manufacturing include polybutadiene, polyisoprene, particularly natural rubber, and copolymers of 1,3-butadiene and styrene. A common feature of these elastomers is that the molar ratio of diene units in the elastomer is generally much higher than 50%, which can make them susceptible to oxidation, particularly under the action of ozone.

[0003] Conversely, the applicant describes a copolymer having a relatively low number of diene units, particularly for the purpose of reducing sensitivity to oxidation phenomena. Another advantage of such a copolymer is the use of ethylene, a commercially available, conventional monomer accessible via fossil or biological routes. Such a copolymer is disclosed, for example, in WO 2007054223. This is a copolymer of 1,3-butadiene and ethylene containing 50 mol% or more of ethylene units. It is synthesized in the presence of a catalyst system containing a neodymium metallocene. The ethylene-rich copolymer of 1,3-butadiene and ethylene is crystalline, and its degree of crystallinity increases with increasing ethylene content. The presence of the crystalline portion imparts high stiffness to the copolymer, which may prove to be excessive for certain applications.

[0004] To reduce the degree of crystallinity of a copolymer of ethylene and 1,3-butadiene, the applicant developed a novel catalyst system as disclosed in WO 2007054224, and a novel copolymer of ethylene and 1,3-butadiene was produced in which the degree of crystallinity was reduced or even eliminated, even with a high ethylene content. This copolymer has the characteristic of containing a 6-membered saturated hydrocarbon cyclic moiety. It was found that the copolymer of ethylene and 1,3-butadiene tends to flow under its own weight. This low-temperature flow is not controlled and, in particular, may cause difficulties in using the copolymer while it is stored in a ball form or in a container.

[0005] The objective of the present invention is to overcome the aforementioned disadvantages.

[0006] This objective is achieved by the present invention, which proposes a branched-chain copolymer containing ethylene and 1,3-butadiene units, said copolymer containing 50 mol% or more of ethylene units and containing a 1,2-cyclohexanediyl moiety.

[0007] Accordingly, the subject of the present invention is a copolymer of ethylene and 1,3-diene containing 50 mol% or more of ethylene units and a 1,2-cyclohexanediyl moiety, wherein the 1,3-diene is 1,3-butadiene or a mixture of 1,3-diene containing 1,3-butadiene, and the copolymer is composed of one main chain and one or more side chains.

[0008] In addition, the present invention relates to a rubber composition comprising a copolymer according to the present invention.

[0009] In addition, the present invention relates to a tire comprising a rubber composition according to the present invention. Specific details for implementing the invention

[0010] In the present invention, any interval of values ​​indicated by the term “between a and b” represents a range of values ​​from greater than “a” to less than “b” (i.e., limits a and b are excluded), and any interval of values ​​indicated by the term “a to b” means a range of values ​​extending from “a” to “b” (i.e., including absolute limits a and b). The abbreviation “phr” means a part by weight per 100 parts by weight of elastomer (total amount of elastomer if multiple elastomers are present).

[0011] The term "based" used to define the components of a catalytic system or composition is understood to mean a mixture of these components, or a product in which some or all of these components react with one another.

[0012] Unless otherwise specified, the content of units resulting from the copolymerization of monomers is expressed as a molar percentage of all units and moiety resulting from the copolymerization of monomers.

[0013] The compounds mentioned in the description may be of fossil origin or bio-based. In the latter case, they may be derived partially or wholly from biomass or obtained from renewable starting materials derived from biomass. This is particularly relevant to elastomers, plasticizers, fillers, etc.

[0014] The copolymer according to the present invention has the essential characteristic of being a copolymer of ethylene and 1,3-diene, wherein the 1,3-diene is 1,3-butadiene or a mixture of 1,3-diene containing 1,3-diene, which means that the monomer unit of the copolymer is produced from the copolymerization of ethylene and 1,3-butadiene or from the copolymerization of a mixture of 1,3-diene containing 1,3-diene and ethylene.

[0015] The copolymer also has the characteristic of containing 50 mol% or more of ethylene units. In a known manner, the term "ethylene unit" is understood to mean a unit having a -(CH2-CH2)- moiety. Preferably, the copolymer contains 60 mol% or more of ethylene units.

[0016] According to one specific embodiment of the present invention, the copolymer contains less than 90 mol% of ethylene units.

[0017] According to one specific embodiment of the present invention, the copolymer contains up to 85 mol% of ethylene units.

[0018] The copolymer also has the essential characteristic of containing a 1,2-cyclohexanediyl moiety. The 1,2-cyclohexanediyl moiety corresponds to chemical formula (I). The presence of the cyclic moiety in the copolymer results from a very specific insertion of ethylene and 1,3-butadiene during copolymerization, as disclosed, for example, in WO 2007054224. Preferably, the copolymer contains up to 15 mol% of the 1,2-cyclohexanediyl moiety. The unit content of the 1,2-cyclohexanediyl moiety in the copolymer depends on the content of ethylene and 1,3-butadiene, respectively.

[0019]

[0020] According to one particularly preferred mode, the 1,3-diene is 1,3-butadiene, and in this case, the copolymer is a copolymer of ethylene and 1,3-butadiene.

[0021] The copolymer according to the present invention also has another essential feature, namely, that it is branched. That is, it consists of one main chain and one or more side chains. Since the copolymer is a copolymer of ethylene and 1,3-diene, the monomer units of the main chain and side chains are produced from the copolymerization of ethylene and 1,3-diene. According to one particularly preferred embodiment, where the 1,3-diene is 1,3-butadiene, the monomer units of the main chain and side chains are produced from the copolymerization of ethylene and 1,3-butadiene.

[0022] Preferably, at least one side chain is attached to the main chain by a covalent bond between a carbon atom of the side chain and a carbon atom of the main chain. More preferentially, the carbon atom involved in the covalent bond to attach the side chain to the main chain is a carbon atom into which ethylene or 1,3-diene is inserted by copolymerization.

[0023] Preferably, the copolymer has a degree of crystallization of less than 20%. More preferentially, the copolymer has a degree of crystallization of less than 10%. More preferentially, the copolymer has a degree of crystallization of less than 5%. Preferably, the copolymer is a statistical copolymer. Preferably, the copolymer is an elastomer. The copolymer is intended to be used, particularly in rubber compositions for tires, especially when it is an elastomer.

[0024] The copolymer according to the present invention is typically prepared by copolymerizing ethylene and 1,3-diene in the presence of a catalyst system, as disclosed in WO 2007054224.

[0025] The catalytic system includes a metallocene of chemical formula (I) and an organomaxin.

[0026] P(Cp 1 Cp 2 )Nd(BH4) (1+y)- L y -N x (I)

[0027] Cp 1 and Cp2 It may be the same or different, and chemical formula C 13 Selected from the group consisting of an unsubstituted fluorenyl group and a substituted fluorenyl group of H8, and

[0028] P is 2 Cp 1 and Cp 2 It is a bridge of energy and ZR 3 R 4 It represents a group, Z represents a silicon or carbon atom, and R 3 and R 4 They may be the same or different, each representing an alkyl group having 1 to 20 carbon atoms, preferably a methyl group, and

[0029] y is an integer, greater than or equal to 0, and

[0030] x is either an integer or a non-integer, is greater than or equal to 0, and

[0031] L represents an alkali metal selected from the group consisting of lithium, sodium, and potassium, and

[0032] N represents a molecule of ether, preferably diethyl ether or tetrahydrofuran, and

[0033] In chemical formula (I), the neodymium atoms are two Cp atoms connected together by a bridge P. 1 and Cp 2 It is connected to a ligand molecule composed of groups. Preferably, the symbol P, denoted by the term bridge, is of the chemical formula ZR 1 R 2 It corresponds to, where Z represents a silicon atom, and R 1 and R 2 may be the same or different and represents an alkyl group having 1 to 20 carbon atoms. More preferentially, bridge P is of the formula SiR 1 R 2 is, R 1 and R 2 is identical and as defined above. More specifically, P corresponds to the chemical formula SiMe2.

[0034] As a substituted fluorenyl group, a fluorenyl group substituted by an alkyl radical having 1 to 6 carbon atoms or by an aryl radical having 6 to 12 carbon atoms may be mentioned. The choice of radical is also guided by the accessibility of the corresponding molecule, which is the substituted fluorene, because the substituted fluorene is commercially available or can be easily synthesized.

[0035] More specifically, as substituted fluorenyl groups, 2,7-di(tert-butyl)fluorenyl groups and 3,6-di(tert-butyl)fluorenyl groups may be mentioned. Positions 2, 3, 6, and 7 each represent the positions of carbon atoms in the ring shown in the following chemical formula, and position 9 corresponds to the carbon atom to which the bridge P is attached.

[0036]

[0037] Preferably, Cp 1 and CP 2 is identical. Advantageously, in chemical formula (I), Cp 1 and CP 2 Each represents a fluorenyl group. The fluorenyl group is represented by the chemical formula C 13 It is H8. Preferably, the metallocene is of the chemical formula (Ia), (Ib), (Ic), (Id), or (Ie), where the symbol Flu is of the chemical formula C 13 It represents the fluorenyl group of H8.

[0038] [{Me2SiFlu2Nd(μ-BH4)2Li(THF)}2] (Ia)

[0039] [Me2SiFlu2Nd(μ-BH4)2Li(THF)] (Ib)

[0040] [Me2SiFlu2Nd(μ-BH4)(THF)] (Ic)

[0041] [{Me2SiFlu2Nd(μ-BH4)(THF)}2] (Id)

[0042] [Me2SiFlu2Nd(μ-BH4)] (Ie)

[0043] The organomas-magnesium compound used as a co-catalyst in a catalytic system is a compound having at least one C-Mg bond. As organomas-magnesium compounds, diorganomas-magnesium compounds, particularly dialkylmagnesium compounds, and organomas-magnesium halides, particularly alkylmagnesium halides, may be mentioned. Diorganomas-magnesium compounds are typically defined by the chemical formula MgR 3 R 4 (Here, R 3 and R 4 is a compound of (which may be the same or different and represents a carbon group). A carbon group is understood to mean a group containing one or more carbon atoms. Preferably, R 3 and R 4 It contains 2 to 10 carbon atoms. More preferentially, R 3 and R 4 Each represents an alkyl group. The organomas-magnesium compound is advantageously a dialkyl magnesium compound, more advantageously butylethyl magnesium or butyloctyl magnesium, and even more advantageously butyloctyl magnesium.

[0044] The catalyst system can be typically prepared by a process similar to that disclosed in patent application WO 2007054224. For example, organomas-magnesium compounds and metallocenes can be reacted in a hydrocarbon solvent for a time between 5 and 60 minutes at a temperature typically in the range of 20°C to 80°C. The catalyst system is generally prepared in an aliphatic hydrocarbon solvent such as methylcyclohexane, or in an aromatic hydrocarbon solvent such as toluene.

[0045] The metallocene used in the manufacture of the catalytic system may be in the form of a crystalline or amorphous powder or in a single-crystal form. The metallocene may be provided in the form of a monomer or a dimer, and these forms follow, for example, the method of manufacturing the metallocene as disclosed in patent application WO 2007054224. The metallocene may typically be prepared by reacting an alkali metal salt of a ligand with a rare earth metal borohydride in a suitable solvent, such as an ether, for example, diethyl ether or tetrahydrofuran, or any other solvent known to those skilled in the art, by a process similar to that disclosed in patent application WO 2007054224, particularly under inert or anhydrous conditions. After the reaction, the metallocene is separated from the reaction byproducts by techniques known to those skilled in the art, such as filtration or precipitation from the second solvent. Finally, the metallocene is dried and isolated in solid form.

[0046] Those skilled in the art adjust the molar ratio of organomagnesium to Nd metal constituting the metallocene according to the desired molar mass of the copolymer. The molar ratio can reach a value of 100, and it is known that a molar ratio of less than 10 is more advantageous for obtaining a polymer with a high molar mass.

[0047] As with all syntheses performed in the presence of organometallic compounds, the synthesis of metallocenes and catalytic systems takes place under an inert atmosphere and anhydrous conditions. Typically, the reaction is carried out starting from anhydrous solvents and compounds under anhydrous nitrogen or argon.

[0048] The catalyst system is generally introduced into a reactor containing a polymerization solvent and a monomer.

[0049] The catalyst system can be typically prepared by a process similar to that disclosed in patent application WO 2007054224. For example, an organomas-magnesium compound and a metallocene are typically reacted in a hydrocarbon solvent at a temperature in the range of 20°C to 80°C for a time period between 5 and 60 minutes. The catalyst system is generally prepared in an aliphatic hydrocarbon solvent such as methylcyclohexane or an aromatic hydrocarbon solvent such as toluene. Generally, after synthesis, the catalyst system is used in this form in the method for synthesizing a copolymer according to the present invention.

[0050] Alternatively, the catalytic system may be manufactured by a process similar to that disclosed in patent application WO 2017093654 A1 or patent application WO 2018020122 A1. According to this alternative, the catalytic system further contains a pre-forming monomer selected from conjugated diene, ethylene, or a mixture of ethylene and conjugated diene, in which case the catalytic system is based at least on a metallocene, an organomagnesium compound, and the pre-forming monomer. For example, the organomagnesium compound and the metallocene are typically reacted in a hydrocarbon solvent for 10 to 20 minutes at a temperature of 20°C to 80°C to obtain a first reaction product, and then the pre-forming monomer selected from conjugated diene, ethylene, or a mixture of ethylene and conjugated diene is reacted with the first reaction product for 1 to 12 hours at a temperature in the range of 40°C to 90°C. Accordingly, the obtained catalyst system can be used immediately in the method according to the present invention, or can be stored under an inert atmosphere before use in the method according to the present invention.

[0051] Those skilled in the art also adjust the polymerization conditions and the concentrations of each reactant (components of the catalyst system, monomers) according to the equipment (devices, reactors) used to carry out polymerization and various chemical reactions. As is known to those skilled in the art, the copolymerization and handling of monomers of the catalyst system and the polymerization solvent(s) take place under an inert atmosphere under anhydrous conditions. The polymerization solvent is typically an aliphatic or aromatic hydrocarbon solvent. The polymerization solvent is preferably aliphatic, advantageously methylcyclohexane.

[0052] The polymerization temperature for obtaining the copolymer according to the present invention is at least 100°C. The conversion rate is high, for example, 90% or more. Preferably, the copolymerization is carried out at a constant ethylene pressure.

[0053] Polymerization can be stopped by cooling the polymerization medium or by adding an alcohol, preferentially an alcohol having 1 to 3 carbon atoms, for example, ethanol. The polymer can be recovered according to conventional techniques known to those skilled in the art, for example by sedimentation, by solvent evaporation under reduced pressure, or by vapor stripping.

[0054] The copolymer according to the present invention is advantageously used in rubber compositions, particularly in tire rubber compositions, especially when it is an elastomer.

[0055] The above-mentioned features of the present invention and other features will be better understood by reading the following description of some exemplary embodiments of the present invention provided as examples without limitation.

[0056] Embodiment of the present invention

[0057] Polymer Characterization Method:

[0058] Nuclear Magnetic Resonance (NMR):

[0059] The copolymer of ethylene and 1,3-butadiene is 1 H and 13It is characterized by 3C NMR spectroscopy. The NMR spectrum is recorded on a Bruker Avance III HD 500 MHz spectrometer equipped with a BBFO z-grad 5 mm "broadband" cryoprobe. Quantitative 1 ¹H NMR experiments use a 30° single-pulse sequence with a 5-second repetition delay between each acquisition. 64 to 256 accumulations are performed. Quantitative 13 10¹³ NMR experiments use a 30° single-pulse sequence with a 10-second repetition delay between proton separation and each acquisition. 10²⁴ to 10²⁴⁴ accumulations are performed. 1 H / 13 C Two-dimensional experiments are used to determine the structure of polymers. The determination of the microstructure of copolymers is based on the literature (Llauro et al., Macromolecules It is defined according to the text of 2001, 34, 6304-6311).

[0060] Intrinsic viscosity:

[0061] The intrinsic viscosity of a 0.1 g / dl polymer solution dissolved in toluene at 25°C is measured starting from the dry polymer solution.

[0062] The intrinsic viscosity is determined by measuring the flow time t of the polymer solution and the flow time t0 of toluene in the capillary. The flow time of toluene and the flow time of the 0.1 g / dl polymer solution are measured in an Uvelohde tube (capillary diameter 0.46 mm, capacity 18 to 22 ml) placed in an automatic temperature-controlled bath at 25 ± 0.1 ℃.

[0063] Intrinsic viscosity is calculated by the following mathematical formula:

[0064] η inh = [ln (t / t0)] / C

[0065] Here,

[0066] C: Concentration of the polymer's toluene solution (g / dl);

[0067] t: Flow time of polymer solution in toluene (seconds); t0: Toluene flow time (seconds);

[0068] η inh : Intrinsic viscosity (dl / g).

[0069] Low-temperature flow:

[0070] The cold flow CF 100(1+6) is the result of the following measurement method:

[0071] It is to measure the weight of rubber extruded through a calibrated die for a given time (6 hours) under fixed conditions (100℃). The diameter of the die is 6.35 mm and the thickness is 0.5 mm.

[0072] The low-temperature flow device is a cylindrical cup with a hole in the bottom. Approximately 40g ± 4g of rubber manufactured in the form of pellets (thickness 2cm, diameter 52mm) is placed in this device. A calibrated piston weighing 1kg (±5g) is placed on the rubber pellets. Afterward, the assembly is placed in a thermally stable oven at 100℃ ± 0.5℃.

[0073] The measurement conditions are not stabilized during the first hour in the oven. After one hour, the extruded product is cut and discarded.

[0074] Afterward, measurements are continued for 6 hours ± 5 minutes, during which time the product is left in the oven. When the 6 hours are finished, a sample of the extruded product must be retrieved by cutting it to the same height as the bottom surface. The test result is the weight of the rubber (g).

[0075] Mooney viscosity:

[0076] Mooney viscosity ML (1+4) at 100°C is measured according to standard ASTM: D-1646.

[0077] A vibration consistency meter is used as described in the standard ASTM D-1646. Mooney plasticity measurements are performed according to the following principle: the composition in its raw state (i.e., before curing) is molded in a cylindrical chamber heated to 100°C. After preheating for 1 minute, the rotor inside the specimen is rotated 2 times per minute, and after rotating for 4 minutes, the operating torque required to maintain this motion is measured. Mooney plasticity (ML 1+4) is expressed in "Mooney units" (MU, 1 MU = 0.83 Nm).

[0078] Degree of crystallization of the polymer:

[0079] Using the standard ISO 11357-3:2011, the crystallization and fusion enthalpies and temperatures of polymers used in differential scanning calorimetry (DSC) are determined. The reference enthalpy of polyethylene is 277.1 J / g (according to the literature (Polymer Handbook, 4th Edition, J. Brandrup, E.H. Immergut and E.A. Grulke, 1999)).

[0080] Synthesis of a copolymer of ethylene and 1,3-butadiene:

[0081] Butyloctyl magnesium (BOMAG) is added to a 70 L reactor containing methylcyclohexane (64 L) and ethylene and 1,3-butadiene in a molar ratio of 8 1 / 29, in the amounts indicated in Table 1, and then the catalyst system is added to the reactor in the amounts indicated in Table 1. At this point, the polymerization reaction is initiated by adjusting the reaction temperature to the temperature indicated in Table 1. The polymerization reaction is carried out at a constant pressure, also indicated in Table 1. The reactor is fed with ethylene and 1,3-butadiene in a molar ratio of 8 1 / 29 throughout the polymerization. The polymerization reaction is stopped by cooling, degassing of the reactor, and the addition of ethanol. An antioxidant is added to the polymer solution. The copolymer is recovered in a constant mass after steam stripping and drying. The average catalytic activity of the catalyst system can be determined from the weighed mass, which is the kilogram of polymer synthesized per hour per mole of neodymium metal (kg / mol·h). - It is displayed as ).

[0082] The catalyst system is a pre-formed catalyst system. It is prepared from 0.0065 mol / L of metallocene [Me2Si(Flu)2Nd(μ-BH4)2Li(THF)] in methylcyclohexane, a co-catalyst, butyloctylmagnesium (BOMAG) (its BOMAG / Nd molar ratio is 2.2), and a pre-formed monomer, 1,3-butadiene (its 1,3-butadiene / Nd molar ratio is 90). The medium is heated at 80°C for 5 hours. It is prepared according to the method of preparation described in paragraph II.1 of patent application WO 2017093654 A1.

[0083] Tests 1 to 9 differ from one another in the amount of co-catalyst used, polymerization pressure, and polymerization temperature. Tests 1 and 2 are examples according to the present invention with a polymerization temperature of 105°C, whereas tests 3 to 9 are examples not according to the present invention, performed at 60°C and 80°C.

[0084] result:

[0085] The characteristics of the copolymers are shown in Table 2.

[0086] Among the copolymers not according to the present invention (Tests 3 to 9), the copolymers of Tests 3, 4, and 9 have very low low-temperature flow values, so their flow tendency over time under their own weight is very low. However, these results are obtained particularly for high Mooney viscosity values ​​of 80 or higher. In fact, it is known that using a polymer with excessively high Mooney viscosity in a rubber composition can make it difficult to extrude the rubber composition, and also require high mixing energy to incorporate the components into the polymer.

[0087] Tests 5 to 8 show that copolymers with lower Mooney viscosity can be obtained, but this implies higher catalyst costs and unfavorable characteristics for storage. In fact, tests 3 to 9 show that the synthesis of copolymers with lower Mooney viscosity requires the use of a larger amount of co-catalyst and inevitably entails an increase in low-temperature flow values.

[0088] The copolymer according to the present invention (Tests 1 and 2) does not exhibit the aforementioned disadvantages. For the same target Mooney viscosity value as the corresponding product synthesized at a lower temperature (Tests 3 to 9), it is obtained using a much smaller amount of co-catalyst and has a much lower low-temperature flow value. Consequently, the copolymer according to the present invention has an improved trade-off between its processability and its flow tendency while making it possible to reduce the catalyst cost of its synthesis. The copolymer according to the present invention has branched specificity, whereas the copolymers of Tests 3 to 9 are linear polymers, as evidenced by the intrinsic viscosity value of the copolymer.

[0089]

[0090]

Claims

Claim 1 A copolymer of ethylene and 1,3-diene containing 50 mol% or more of ethylene units and a 1,2-cyclohexanediyl moiety, wherein the 1,3-diene is 1,3-butadiene or a mixture of 1,3-diene containing 1,3-butadiene, and the copolymer comprises one main chain and one or more side chains. Claim 2 A copolymer according to claim 1, wherein at least one side chain is attached to the main chain by a covalent bond between a side chain carbon atom and a main chain carbon atom. Claim 3 In paragraph 2, the carbon atom involved in the covalent bonding so that the side chain is attached to the main chain is a carbon atom produced by the insertion of ethylene or 1,3-diene into the copolymer by copolymerization, a copolymer. Claim 4 A copolymer according to any one of claims 1 to 3, wherein the 1,3-diene is 1,3-butadiene. Claim 5 In paragraph 4, the copolymer is a copolymer containing up to 15 mol% of a 1,2-cyclohexanediyl moiety. Claim 6 In any one of paragraphs 1 to 3, the copolymer is a copolymer containing less than 90 mol% of ethylene units. Claim 7 A copolymer in any one of paragraphs 1 to 3, wherein the copolymer is a statistical copolymer. Claim 8 A copolymer having a degree of crystallization of less than 20% in any one of claims 1 to 3. Claim 9 A rubber composition comprising a copolymer according to any one of claims 1 to 3. Claim 10 A tire comprising a rubber composition according to paragraph 9. Claim 11 delete Claim 12 delete Claim 13 delete Claim 14 delete Claim 15 delete

Citation Information

Patent Citations

  • Monofunctional or telechelic copolymer of 1,3-butadiene and ethylene

    KR1020180090870A

  • Rubber composition comprising a highly saturated diene elastomer

    US20150353716A1

  • Monofunctional or telechelic copolymer of 1,3-butadiene and ethylene

    WO2017097831A1

  • Borohydride Metallocene Complex of a Lanthanide, Catalytic System Including Said Complex, Polymerization Method Using Same and Ethylene / Butadiene Copolymer Obtained Using Said Method

    US20100022725A1